What Does the Critical Environmental IPE Perspective Contribute to Our Understanding of IPE? - Zhang, Jingjing (Journal of Theory and Practice in Economics and Management, 2024)
The environmental perspective within the international political economy (IPE) highlights the importance of environmental protection in modern society and aids in our comprehension of IPE, particularly in terms of environmental economics. The environment and economy are closely intertwined. From an environmental IPE standpoint, we observe market failures and externalities that conflict with neoliberal principles. Governments often address these issues by using taxes and subsidies to internalize externalities, thereby attempting to balance environmental and economic concerns. However, critical environmental IPE extends beyond traditional environmental economics. Constrained by natural resources and ecological carrying capacity, as well as the diminishing demographic dividend, the extensive mode of economic growth is unsustainable and may no longer be viable. To improve the global ecological environment and promote harmonious development among nature, the economy, and society, transforming the mode of economic growth is essential. A zero-growth economy represents a transitional phase connecting two different modes of economic growth and plays a crucial role in mitigating socioeconomic contradictions. Ecological economics differs from environmental economics by adopting a more complex approach to environmental issues, focusing on long-term sustainability and scale considerations. This essay aims to construct an analytical framework to discuss the environmental IPE perspective and its contribution to our understanding of IPE.